Aggressive fibromatosis-associated with papillary thyroid cancer: two cases and a brief review - Li, Yao; Li, Shichao; Qi, Xiaowei; Fu, Wenying; Zhang, Fan; Yang, Xinhua (Translational Cancer Research, 2019)
Aggressive fibromatosis (AF) is usually considered a benign tumor. Reports of the association between AF and malignancies have appeared infrequently. Herein, we report two cases of AF arising in the neck that were associated with papillary thyroid cancer. Two cases are presented in this article. One is a 31-year-old male patient who was diagnosed with AF 9 months after his thyroid cancer operation; there has been no recurrence after surgical resection and postoperative radiotherapy. The other is a 53-year-old female patient who was diagnosed with thyroid cancer and AF simultaneously. There is still no recurrence after surgical resection, endocrine therapy and thyroid-stimulating hormone (TSH) suppression treatment. Both cases showed β-catenin positivity upon further immunohistochemistry (IHC) examination. AF is a rare and benign tumor. It can occur in association with malignancies, such as thyroid cancer. Whether a patient diagnosed with AF associated with thyroid cancer has a family history of a familial adenomatous polyposis (FAP) mutation or β-catenin mutation should be given more attention. The treatment strategy in this situation includes surgical excision combination with radiotherapy and endocrine therapy to reduce the recurrence rate.